Peran Guru BK dalam Membentuk Karakter Siswa Melalui Layanan BK Kelompok - wati, misra (PEMBELAJAR: Jurnal Ilmu Pendidikan, Keguruan, dan Pembelajaran, 2017)
Abstract : The existence of guidance and counseling teachers in schools have an important role to shape the character of students, helping any problems experienced by the students, and have the task of developing psychological and social aspects of students. Character is the nature or character of oneself that is unique to everyone as a result of a pattern of behavior, norms and morals that formed positively. In the aspect of character education, all that does is actually located on the affective and psychomotor contact with the character education. Improved guidance and counseling services in schools in this group bk services is one form of educational activities for the achievement of national education goals.